2013
DOI: 10.1073/pnas.1310501111
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic KIT-containing exosomes increase gastrointestinal stromal tumor cell invasion

Abstract: During tumor development, constant interplay occurs between tumor cells and surrounding stromal cells. We report evidence that gastrointestinal stromal tumor (GIST) cells invade the interstitial stroma through the release of the oncogenic protein tyrosine kinase (KIT)-containing exosomes, which triggers the phenotypic conversion of progenitor smooth muscle cells to tumor-promoting cells. These recipient cells display morphologic changes and acquire tumor-associated phenotypes, including enhanced adhesion to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(118 citation statements)
references
References 32 publications
(32 reference statements)
7
111
0
Order By: Relevance
“…Conversely, ␤ 1 integrin subunit levels do not show any detectable change upon exosome uptake in the recipient cells; the reasons why this occurs remain to be investigated. Third, this is the only study showing surface re-expression of a transmembrane receptor of the integrin family; two previous studies have shown that two different transmembrane receptors, MET and KIT, are transferred and re-expressed on the surface of recipient cells (9,38). Finally, our study is the first to show that the ␣ v ␤ 6 integrin that is transferred between different subsets of PrCa cells is functional and promotes cell adhesion and migration on LAP-TGF␤ in an ␣ v ␤ 6 integrin-dependent manner.…”
Section: Discussionmentioning
confidence: 93%
“…Conversely, ␤ 1 integrin subunit levels do not show any detectable change upon exosome uptake in the recipient cells; the reasons why this occurs remain to be investigated. Third, this is the only study showing surface re-expression of a transmembrane receptor of the integrin family; two previous studies have shown that two different transmembrane receptors, MET and KIT, are transferred and re-expressed on the surface of recipient cells (9,38). Finally, our study is the first to show that the ␣ v ␤ 6 integrin that is transferred between different subsets of PrCa cells is functional and promotes cell adhesion and migration on LAP-TGF␤ in an ␣ v ␤ 6 integrin-dependent manner.…”
Section: Discussionmentioning
confidence: 93%
“…These exosomes contain large amount of tumorpromoting RNAs (mRNAs, miRNAs and other non-coding RNAs) and proteins (EGFR, HSPs, KIT, etc.). [14][15][16] Exosomemediated exchange of mRNAs and miRNAs (named as exosomal shuttle RNA, esRNA) is believed to be a novel way for genetic intervention between cells. 17 Plenty of miRNAs had been detected in exosomes.…”
Section: Overview Of Exosomes In Cancer Progressionmentioning
confidence: 99%
“…Recent evidence highlights the role of EVs, in particular exosomes, to stimulate invasion and migration in various cancer models [151]. For example, breast MCF-7-derived exosomes were shown to foster tumour growth, migration, and matrix degradation, via secretory Rab27b [152].…”
Section: Exosomes Enhance Cell Migration and Invasionmentioning
confidence: 99%